Effects of whole-body vibration on muscle strength and power of elderly: A systematic review - Monique Opuszcka Campos; Paulo Sergio Chagas Gomes (Desafio Singular, 2014)
The aim of this systematic review was to summarize available scientific evidence on the utilization of whole body vibration as an alternative method to promote effective modifications on muscle strength and power in the aging population.  Scientific studies were retrieved from the following databases: Medline, Scielo, Lillacs, Cochrane Library, PEDro and Science Citation Index. The PEDro scale was used to assess the quality of the included studies, while content went through a critical analysis. From the 91 studies retrieved, 75 were excluded and 16 attended the selection criteria. From the16, the majority (68.8%) presented from moderate to high methodological quality. Whole-body vibration associated to both isometric and dynamic exercises seemed to constitute an alternative for therapeutic intervention to improve muscular strength and power of healthy elderly. However, due to the characteristics of the designs of the studies reviewed and the threats to their internal validity (i.e., the absence of the control condition to the vibratory stimulus) it was challenging to establish the additional effects of the whole-body vibration on the target population. Divergent findings were found for the whole-body vibration effect on muscular power. It is still necessary to conduct randomized control trials to establish the real effectiveness of this kind of intervention.